2020
DOI: 10.3390/ijms21155292
|View full text |Cite
|
Sign up to set email alerts
|

Halophytic Hordeum brevisubulatum HbHAK1 Facilitates Potassium Retention and Contributes to Salt Tolerance

Abstract: Potassium retention under saline conditions has emerged as an important determinant for salt tolerance in plants. Halophytic Hordeum brevisubulatum evolves better strategies to retain K+ to improve high-salt tolerance. Hence, uncovering K+-efficient uptake under salt stress is vital for understanding K+ homeostasis. HAK/KUP/KT transporters play important roles in promoting K+ uptake during multiple stresses. Here, we obtained nine salt-induced HAK/KUP/KT members in H. brevisubulatum with different expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The HvHAK1 gene, which encodes a high-affinity potassium transporter, was the first KUP/HAK/KT gene in higher plants to be cloned [ 71 ]. Since then, various homologs of HvHAK1 have been identified and characterized, including AtHAK5 , OsHAK1 , OsHAK5 , ZmHAK5 , and HbHAK1 [ 18 , 19 , 20 , 23 , 72 ]. The expression levels of these genes are up-regulated significantly under LK conditions as part of a common plant adaptive response to LK stress.…”
Section: Discussionmentioning
confidence: 99%
“…The HvHAK1 gene, which encodes a high-affinity potassium transporter, was the first KUP/HAK/KT gene in higher plants to be cloned [ 71 ]. Since then, various homologs of HvHAK1 have been identified and characterized, including AtHAK5 , OsHAK1 , OsHAK5 , ZmHAK5 , and HbHAK1 [ 18 , 19 , 20 , 23 , 72 ]. The expression levels of these genes are up-regulated significantly under LK conditions as part of a common plant adaptive response to LK stress.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, by studying two contrasting C. quina accessions, Kiani-Pouya et al [ 95 ] have recently revealed that the transcript levels of CqGORK in roots remained unchanged or decreased in salt-tolerant accession but increased in salt-sensitive accession, implying GORK’s role in K + retention for better osmotic adjustment in the cells of salt-sensitive C. quina . Furthermore, the ion selectivity approach of HAKs/HKTs has been reported to confer greater uptake of K + in Eutrema parvula [ 105 ] and Hordeum brevisubulatum [ 99 ] and, thus, contributed to improved K + /Na + homeostasis ( Table 1 ). Nonetheless, future studies should be taken to decipher how the movement of K + between intra-cellular and inter-cellular membranes by K + transporters contribute to the adjustment of the osmotic environment in salt-exposed halophytic plants.…”
Section: Biochemical Mechanisms Associated With Halophyte Adaptation To Salinitymentioning
confidence: 99%
“…OsHKT1 transports Na + into root cells in rice, compensating for K + deficiency ( Horie et al, 2001 ). Overexpression of StNHX1, OsHAK5 , and HbHAK1 makes plants highly tolerant to salt stress ( Chen et al, 2014 ; Zhang et al, 2020 ; Horie et al, 2011 ). The SOS (salt overly sensitive) signaling pathway is a well-studied pathway closely related to plant salt tolerance ( Qiu et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%